The Spectral Petrov-Galerkin Method for Solving Integral Equations of the First Kind (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The major goal of this research is to use the spectral Petrov-Galerkin method (SPGM) to solve the first type ofVolterra integral equations (VIEs). Three examples will be given to demonstrate how the suggested technique works, incomparison to the examples in [1] and [11], where the numerical and exact solutions are quite harmonic, effectively indicatingthe numerical answers. The absolute errors were determined to estimate the validity of the suggested method and todemonstrate that it was an effective and valid method.